1972
DOI: 10.1037/h0033530
|View full text |Cite
|
Sign up to set email alerts
|

Spaced-trials reward magnitude effects in the rat: Single versus multiple food pellets.

Abstract: Sixty rats were trained in a runway with either small-or large-reward magnitude. Both small and large rewards were presented in single-or multiplepellet form. One training trial was given each day for 120 days. Early in training the large-reward animals ran faster than those receiving small reward and the effect was more pronounced in the multiple-pellet condition. Later in training the small-reward animals equaled the performance of the animals receiving large reward and even ran somewhat faster in the run se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 2 publications
4
20
1
Order By: Relevance
“…There now exists a very substantial body of evidence indicating that under these conditions any initial acquisition differences due to reward magnitude disappear after extended training (e.g., Black, 1969;Campbell, Batsche, & Batsche, 1972;McCain, 1970;McCain et aI., 1971;McCain et aI., 1976;Shanab, France, & Young, 1976). Similar effects were seen when different magnitudes of 50% reward were given (Capaldi & Freese, 1974;McCain, 1970;Meyers & Anderson, 1975).…”
supporting
confidence: 53%
“…There now exists a very substantial body of evidence indicating that under these conditions any initial acquisition differences due to reward magnitude disappear after extended training (e.g., Black, 1969;Campbell, Batsche, & Batsche, 1972;McCain, 1970;McCain et aI., 1971;McCain et aI., 1976;Shanab, France, & Young, 1976). Similar effects were seen when different magnitudes of 50% reward were given (Capaldi & Freese, 1974;McCain, 1970;Meyers & Anderson, 1975).…”
supporting
confidence: 53%
“…It was pointed out that studies by Black (1969) and Campbell, Batsche, and Batsche (1972) have been reported in which satiation effects were taken into account and reward magnitude effects failed to develop. We again would agree with McCain, Ward, and Lobb that it is nice "to have a colleague in another laboratory examine the possible effects of satiation."…”
mentioning
confidence: 99%
“…At best, the once widely held assumption that large magnitudes result in superior performance appears to be on somewhat shaky ground. Data reported by Black (1969), Campbell, Batsche, and Batsche (1972), McCain (1970), andMcCain, Dyleski, andMcElvain (1971) have suggested, rather convincingly, that under some conditions reward magnitude effects may be rather transitory, if they develop at all.…”
Section: Texas Christian University Fort Worth Texas 76129mentioning
confidence: 98%